The Metaphysical Morality of Francis Hutcheson: A Consideration of Hutcheson’s Critique of Moral Fitness Theory - Sheridan, Patricia (Sophia, 2007)
Hutcheson’s theory of morality shares far more common ground with Clarke’s morality than is generally acknowledged. In fact, Hutcheson’s own view of his innovations in moral theory suggest that he understood moral sense theory more as an elaboration and partial correction to Clarkean fitness theory than as an outright rejection of it. My aim in this paper will be to illuminate what I take to be Hutcheson’s grounds for adopting this attitude toward Clarkean fitness theory. In so doing, I hope to bring to light an otherwise unexpected continuity between moral sense theory and the moral rationalism to which it is usually opposed, and, in so doing, draw attention to the anti-sceptical realism that lies at the heart of both accounts.